Purification and properties of a low molecular weight 1,4-beta-D-glucan glucohydrolase having one active site for carboxymethyl cellulose and xylan from an alkalothermophilic Thermomonospora sp - Jagtap, Sharmili; Rao, M (Biochemical and Biophysical Research Communications, 2005)
A low molecular weight 1,4-beta-D-glucan glucohydrolase from an extracellular culture filtrate of Thermomonospora sp. was purified to homogeneity. The molecular weight of the purified enzyme was 14.2 kDa by MALDI-TOF analysis and is in agreement with SDS-PAGE and gel filtration chromatography. The purified enzyme exhibited both endocarboxymethyl cellulase and endoxylanase activities. A kinetic method was employed to study the active site of the enzyme that hydrolyzes both carboxymethyl cellulose and xylan. The experimental data coincide well with the theoretical values calculated for the case of a single active site. Conformation and microenvironment at the active site was probed with fluorescent chemo-affinity labeling using o-phthalaidehyde as the chemical initiator. Formation of isoindole derivative resulted in complete inactivation of the enzyme to hydrolyze both xylan and CMC as judged by fluorescence studies corroborating a single active site for the hydrolysis of xylan and CMC. (C) 2005 Elsevier Inc. All rights reserved.
Keywords: Cellulase; CMC; OPTA; single active site; Thermomonospora sp.; xylan; Xylanase

Conformation and microenvironment of the active site of a low molecular weight 1,4-beta-D-glucan glucanohydrolase from an alkalothermophilic thermomonospora sp.: involvement of lysine and cysteine residues - Jagtap, Sharmili; Rao, Mala (Biochemical and Biophysical Research Communications, 2006)
Conformation and microenvironment at the active site of 1,4-beta-D-glucan glucanohydrolase was probed with fluorescent chemo-affinity labeling using o-phthalaldehyde. OPTA has been known to form a fluorescent isoindole derivative by cross-linking the proximal thiol and amino groups of cysteine and lysine. Modification of lysine of the enzyme by TNBS and of cysteine residue by PHMB abolished the ability of the enzyme to form an isoindole derivative with OPTA. Kinetic analysis of the TNBS and PHMB-modified enzyme suggested the presence of essential lysine and cysteine residues, respectively, at the active site of the enzyme. The substrate protection of the enzyme with carboxymethylcellulose (CMC) confirmed the involvement of lysine and cysteine residues in the active site of the enzyme. Multiple sequence alignment of peptides obtained by tryptic digestion of the enzyme showed cysteine is one of the conserved amino acids corroborating the chemical modification studies. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: 1; 4-beta-D-glucan glucanohydrolase; active site microenvironment; Cysteine; lysine; OPTA; PHMB; Thermomonospora sp.; TNBS

Crystallization and preliminary X-ray characterization of a thermostable low-molecular-weight 1,4-beta-D-glucan glucohydrolase from an alkalothermophilic thermomonospora sp. - Manikandan, K.; Jagtap, Sharmili; Rao, M.; Ramakumar, S. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2006)
{Cellulases catalyze the hydrolysis of beta-1,4-glycosidic linkages within cellulose, the most abundant organic polymer on earth. The cellulase (TSC; EC 3.2.1.4) from an alkalothermophilic Thermomonospora sp. has a low molecular weight of 14.2 kDa. It is optimally active at 323 K and stable over the wide pH range of 5 - 9. Moreover, it has bifunctional activity against cellulose and xylan polymers. In this study, TSC was purified from the native source and crystallized by the hanging-drop vapour-diffusion method. The crystals belong to the orthorhombic space group P2(1)2(1)2(1), with unit-cell parameters a = 49.9

Fluorescence study on interactions of alpha-crystallin with the molten globule state of 1, 4-beta-D-glucan glucanohydrolase from thermomonospora sp induced by guanidine hydrochloride - Jagtap, Sharmili; Rao, Mala (Journal of Fluorescence, 2009)
In this paper, the interaction between alpha- crystallin and molten globule structure of 1,4-beta-D-Glucan Glucohydrolase (TSC) from an alkalothermophilic Thermomonospora sp. was investigated mainly by fluorescence quenching spectra, circular dichroism and three dimensional fluorescence spectra under simulative physiological conditions. Denaturation studies using GdnCl indicated that TSC folds through a partially folded state that resembles molten globule at 1.8 M GdnCl. The chaperone activity of alpha- crystallin was employed to study refolding of TSC. Here we studied the refolding of GdnCl denatured TSC from its molten globule state (TSC-m complex) in the presence and absence of alpha-crystallin to elucidate the molecular mechanism of chaperone-mediated in vitro folding. Our results, based on intrinsic tryptophan fluorescence and ANS binding studies, suggest that alpha-crystallin formed a complex with a putative intermediate molten globule - like intermediate in the refolding pathway of TSC. Reconstitution of the active TSC was observed on cooling the alpha-crystallin aEuro cent TSC -m complex to 4A degrees C. Addition of alpha-crystallin to the molten globule - like intermediate of TSC (TSC-m complex) complex initiated the refolding of TSC with 69 % recovery of the biological activity of the enzyme.
Keywords: ANS; Cellulase; Guanidine hydrochloride; Protein folding

Conducting polyanilline based paints on hot dip galvanized low carbon steel for corrosion protection - Deshpande, P.; Vagge, S.; Jagtap, Sharmili; Khiarnar, R.; Kelkar, Sarika A.; More, Minal (Bulgarian Chemical Communications, 2012)
Conducting polyaniline based paints have been applied on hot dip galvanized low carbon steel samples. The corrosion protection performance of these paint coatings was evaluated by using Tafel plots and impedance spectroscopy. It was found that the paint coatings offered significant corrosion protection to hot dip galvanized low carbon steel in aqueous 3.5 wt % NaCl solution.
Keywords: Conducting polyaniline based paints; corrosion prevention; hot dip galvanized low carbon steel